Community participation in watershed management programs - Bagherian, Reza; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ahmad, Shamsuddin (Science Publications, 2009)
Problem statement: Several studies in other countries had shown the influence of socio demographic, knowledge, satisfaction and attitudinal factors in level of community participation in development programs. The question here is, whether these factors would also be effective on community participation in WMP in Iran? Objective: Determine the factors which are influence community participation in order to enhance their participation in Watershed Management Programs (WMP) in Iran. Approach: A cross sectional survey design was carried out for this study. Data were collected from 200 respondents which are randomly selected from three villages in Hable-Rud basin. Data were gathered through personal interviews by using a questionnaire. Descriptive analysis, Pearson correlation analysis and regression analysis were employed to analyze the data. Results: Findings of this study showed that satisfaction of prior programs had highest relationship with level of participation (r = 0.518, p = 0.000), and followed by attitude toward WMP (r = 0.489, p = 0.000) knowledge of WMP (r = 0.435, p = 0.000), total monthly income (r = 0.177, p = 0.012) and alternative monthly income (r = 0.158, p = 0.025). However multiple regression analysis discovered that, four independent variables are important for explaining variation in the level of participation. These variables were; satisfaction of prior programs, attitude toward WMP, knowledge of WMP and alternative monthly income, and these variables explained 43.6% of variation in level of participation. Conclusion/Recommendations: The results of this study indicated that high level of satisfaction of prior programs, positive attitude toward WMP, high knowledge of WMP and high level of alternative income increase level of community participation in WMP in Iran. This study also provided a number of implications and recommendations to increase the level of community participation in WMP.